Correction: Neural recordings can differentiate between spontaneously metastasizing melanomas and melanomas with low metastatic potential. - Jay Shiralkar; Tiana Anthony; Grant A McCallum; Dominique M Durand (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297281.].